Free-standing thick-film piezoelectric multimorph cantilevers for energy harvesting - Kok, Swee Leong; White, Neil; Harris, Nick (2008)
Piezoelectric materials provide one approach for converting mechanical to electrical energy and can therefore be used to harvest energy from ambient vibration sources. Typically, piezoelectric materials are fabricated onto thin substrates, such as aluminum and stainless steel. These serve as mechanical support platforms to function as a cantilever beam structure. The platforms, however, are non-electro-active and they do not contribute directly to the electrical power output. The aim of this paper is to describe a novel multimorph cantilever structure in a free-standing form. Multimorphs consist of three laminar sections of lead zirconate titanate (PZT) of equal thickness 40 Â¿m and length 18 mm were polarized in two modes; series and parallel. An optimum output power of 42 Â¿W was measured when the series polarized sample was excited at its resonant frequency of 400 Hz.